The Accessory Gene saeP of the SaeR/S Two-Component Gene Regulatory System Impacts Staphylococcus aureus Virulence During Neutrophil Interaction - Collins, Madison M.; Behera, Ranjan K.; Pallister, Kyler B.; Evans, Tyler J.; Burroughs, Owen; Flack, Caralyn; Guerra, Fermin E.; Pullman, Willis; Cone, Brock; Dankoff, Jennifer G.; Nygaard, Tyler K.; Brinsmade, Shaun R.; et al. (Frontiers in Microbiology, 2020)
Staphylococcus aureus (S. aureus) causes a range of diseases spanning from superficial skin and soft-tissue infections to invasive and life-threatening conditions (Klevens et al., 2007; Kobayashi et al., 2015). S. aureus utilizes the Sae sensory system to adapt to neutrophil challenge. Although the roles of the SaeR response regulator and its cognate sensor kinase, SaeS, have been demonstrated to be critical for surviving neutrophil interaction and for causing infection, the roles for the accessory proteins SaeP and SaeQ remain incompletely defined. To characterize the functional role of saeP and saeQ during innate immune interaction, we generated isogenic deletion mutants lacking these accessory genes in USA300 (USA300saeP and USA300saeQ). S. aureus survival was increased following phagocytosis of USA300saeP compared to USA300 by neutrophils. Additionally, secreted extracellular proteins produced by USA300saeP caused significantly more plasma membrane damage to human neutrophils than extracellular proteins produced by USA300. Deletion of saeQ resulted in a similar phenotype, but effects did not reach significance during neutrophil interaction. The enhanced cytotoxicity of USA300saeP toward human neutrophils correlated with an increased expression of bi-component leukocidins known to target these immune cells. A double mutant of saeP and saeQ (USA300saePQ) showed a significant increase in survival following neutrophil phagocytosis that was comparable to the USA300saeP single mutant and increased the virulence of USA300 during murine bacteremia. These data provide evidence that SaeP modulates the Sae-mediated response of S. aureus against human neutrophils and suggest that saeP and saeQ together impact pathogenesis in vivo.